2022
DOI: 10.24057/2071-9388-2021-082
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Analysis Of The Ural Power Grid Vulnerability To The Impact Of Sleet And Wind

Abstract: In this paper, we describe an experiment of complex power grid structure and wind and sleet mapping of territory using two different network indices: standard edge betweenness centrality and new author’s index – electrical grid centrality. Such analysis of the network allows to identify power lines with high load which could be vulnerable elements of the power grid. It is very important for strategic planning of power grids to reduce the risk of accidents by distributing loads across several lines so that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Based solely on structural data of the grid, 23,24 previous works showed that it is possible to mitigate widespread outages caused by terrorist attacks 25 and extreme weather events. 26,27 Recent works have then provided a more reliable analysis of the power-grid vulnerability by incorporating other static (line impedance, nominal power) and dynamic (power flow) characteristics of the power grid. 9,28,29 Complex network models, such as small-world 30 and scalefree 31,32 networks, play a key role in assessing the robustness of different types of network structures to random and targeted attacks.…”
Section: Articlementioning
confidence: 99%
“…Based solely on structural data of the grid, 23,24 previous works showed that it is possible to mitigate widespread outages caused by terrorist attacks 25 and extreme weather events. 26,27 Recent works have then provided a more reliable analysis of the power-grid vulnerability by incorporating other static (line impedance, nominal power) and dynamic (power flow) characteristics of the power grid. 9,28,29 Complex network models, such as small-world 30 and scalefree 31,32 networks, play a key role in assessing the robustness of different types of network structures to random and targeted attacks.…”
Section: Articlementioning
confidence: 99%